2017
DOI: 10.6002/ect.mesot2016.p52
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Traumatic neuromas of the biliary tract have occasionally been reported to cause strictures at the cystic duct stump as a late complication of cholecystectomy with common bile duct exploration. The incidence of symptomatic traumatic biliary neuroma appears to be low after orthotopic liver transplant, as only 25 patients have been described previously in the English-language literature. Traumatic (amputation) neuroma is a reactive proliferation of pericholangial nerve fibers induced by injury, but it is not a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…However, traumatic neuroma arising in the gallbladder is a rare occurrence ( 15 ). Moreover, due to sustained injuries, traumatic neuroma can occur after orthotopic liver transplantation ( 16 , 17 ). Rarely, traumatic neuroma might arise in the gallbladder post-vagotomy ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, traumatic neuroma arising in the gallbladder is a rare occurrence ( 15 ). Moreover, due to sustained injuries, traumatic neuroma can occur after orthotopic liver transplantation ( 16 , 17 ). Rarely, traumatic neuroma might arise in the gallbladder post-vagotomy ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Herrera et al [23] reported 15 cases of traumatic neuromas that were detected between 1 and 17 months after transplantation (median: 4 months) either during surgery for obstructive jaundice (12 cases) or after alterations of liver function tests (2 cases), or incidentally discovered after retransplantation (1 case). It has been concluded that biliary stricture after orthotopic liver transplantation occurs in 3.5–10% of the cases [4, 23, 30, 36]. Thus, they should be considered in the differential diagnosis of late biliary strictures after orthotopic liver transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…They include adenomas, carcinoid tumors, and tumors of the supporting connective tissue structures such as granular cell tumors, leiomyomas, lipomas, neurofibromas, schwannomas, or neuromas [1]. Neuromas arising in the biliary tree are rare, with approximately 100 cases reported in the English literature so far [2-4]. They are mostly localized in the extrahepatic bile duct due to the abundant anastomotic network of sympathetic and parasympathetic nerve fibers and small nerves accompanying blood vessels from branches of the hepatic and gastroduodenal arteries [5].…”
Section: Introductionmentioning
confidence: 99%
“…Until now, 251 cases of traumatic neuroma have been described in the PubMed database. They can occur in any location, not only in the limbs, but also in the visceral and cranial nerves [4]. From a radiological point of view, the differential diagnosis of the lesion includes Morton neuroma (no history of prior trauma or surgery and the involved nerve stays intact), mucosal neuromatosis (but they a usually multiple), solitary circumscribed neuroma (mostly affect the face and are usually located in dermis and there is no history of prior trauma or surgery), as well as neurofibroma and schwannoma (neither trauma, nor surgery are present) [2,5].…”
Section: Current Issues In Pharmacy and Medical Sciencesmentioning
confidence: 99%
“…The available methods include conservative treatment (opioids and non-opioid analgesic, antidepressants, anticonvulsants), minimally invasive procedure (cryoablation or direct injection of corticosteroid, ethanol, phenol) as well as the total excision. Various alternative methods such as acupuncture, physical therapy, neuromodulation has also been suggested [1][2][3][4].…”
Section: Current Issues In Pharmacy and Medical Sciencesmentioning
confidence: 99%